Rudolf II. a jeho pád - Novák, Johann Frdr (Knihovna sněmů českých, 1935)
An in-depth study on the life of Rudolf II, 1552-1612, Holy Roman emperor, concentrating on the circumstances surrounding his fall in 1612.